2021
DOI: 10.1039/d1fo01429c
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids obtained from an ionic liquid-mediated process display anti-inflammatory response in the adipose tissue-liver axis

Abstract: Ionic liquids (ILs) have been proposed as more efficient and sustainable solvents to replace volatile organic solvents (VOS). However, the drawbacks associated to their use are still limiting the regular...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 53 publications
2
6
0
4
Order By: Relevance
“…Additionally, the low adiponectin levels have been reported to stimulate the endothelial cyclooxygenase 2 (COX-2) and are related to renal dysfunction and proteinuria ( Tesauro, Mascali, Franzese, Cipriani, Cardillo & Di Daniele, 2012 ). In our previous work ( de Souza Mesquita, Casagrande et al, 2021d ), we demonstrated that the adiponectin level corroborates this work's findings since animals supplemented with VOS-carotenoids have a lower level compared to those supplemented with IL-carotenoids, independent of the diet (Control or HFD). It states that obesity itself might be a trigger factor to kidney diseases and a molecular inflammatory derangement.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Additionally, the low adiponectin levels have been reported to stimulate the endothelial cyclooxygenase 2 (COX-2) and are related to renal dysfunction and proteinuria ( Tesauro, Mascali, Franzese, Cipriani, Cardillo & Di Daniele, 2012 ). In our previous work ( de Souza Mesquita, Casagrande et al, 2021d ), we demonstrated that the adiponectin level corroborates this work's findings since animals supplemented with VOS-carotenoids have a lower level compared to those supplemented with IL-carotenoids, independent of the diet (Control or HFD). It states that obesity itself might be a trigger factor to kidney diseases and a molecular inflammatory derangement.…”
Section: Discussionsupporting
confidence: 87%
“…Notably, the high-fat diet (HFD) model efficiently induced body gain mass during the experimental period associated with hyperphagia and increased caloric intake ( de Souza Mesquita, Casagrande et al, 2021d ). The fast body mass gain reproduces an obesity induction model, which promotes the development of other non-communicable diseases such as cardiovascular diseases, diabetes, and kidney failure ( Kiortsis and Christou, 2012 , da Silva Junior et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations